The Study Of Human Organisation And Technology Factors Influence On Hospital Information System Satisfaction In Malaysia - Lee, Heng Wei (2013)
This study aimed to understand the issues and barriers pertaining to ICT adoption in healthcare in Malaysia. There are very few studies of HIS adoption available in the literature, especially in Malaysia context. In addition, existing studies are mostly focused on a single perspective, either on the user perspective, organisation perspective or the technology itself in order to understand the factors which influence the adoption of information systems in the healthcare industry. Therefore, this study extended the Human-Organization-Technology Fit Framework to examine the HIS adoption in Malaysia by integrating human factors (computer self-efficacy and prior experience), organizing factors (subjective norms and facilitating conditions), and technology factors (perceived usefulness and perceived ease of use).